PHENOMENON OF PHOTO EFFECT IN SEMICONDUCTORS - Oripova Dilnoza Karimjon kizi; Yusupov Abdurashid Khamidillaevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: This article describes the phenomenon of photoeffect in semiconductors, its theoretical foundations, types and practical application. The internal and external types of photoeffect, their mechanism and the processes occurring in p-n junction, photodiode and photoresistor are explained in detail. Also, special attention is paid to its application in solar cells, optical communication systems and other fields.